Assessment of Riparian Ecosystem Health in the Tamiang River, Aceh, Indonesia as Remains Habitat of Batagur borneoensis (Schlegel & Muller, 1844): Riparian Habitat Quality for Tuntong Laut (Batagur borneoensis) - Saputra, Syifa; Arisoesilaningsih, Endang; Kurniawan , Nia; Retnaningdyah, Catur (Journal of Tropical Life Science, 2023)
The riparian zone along the Tamiang River, Aceh Province, is an important habitat for the survival of the tuntong laut (Batagur borneoensis) which is already threatened with extinction. This study aims to evaluate the quality and role of the riparian zone as a habitat for B. borneoensis along the Tamiang River, which can then be used as a reference in conservation. Riparian habitat quality was assessed by calculating the Qualitat del Bosc de Ribera (QBR) index, which was determined based on the total riparian cover, cover structure, cover quality, and channel alteration. In addition, observations of water quality (salinity, turbidity, and dissolved oxygen (DO)) and the number of riparian vegetation species were also carried out. Monitoring was carried out at five stations: Iyu River, Kampung Baru, Batang Lawang, Pusong Kapal Dermaga, and Pusong Kapal. The results showed variations in water quality between locations with DO and turbidity levels exceeding the quality standards set by the government. The richness of the types of riparian vegetation found ranged from 0-8 species (seedlings), 2-7 species (saplings), and 1-4 species (poles). The quality of riparian habitats in all study locations experienced significant degradation, including the euhemerobic and polyhemerobic (Hemeroby) categories, Cultural assisted system and Semi-transformed system (Naturalness), and Extreme degradation to poor-fair quality (QBR). The presence of B. borneoensis in the research location can adapt to the poor quality of riparian habitat. However, the density decreases significantly at higher salinity.